Analysis of a genomic DNA region from the cyanobacterium Synechococcus sp. strain PCC7942 involved in carboxysome assembly and function. - Price, G D (1993)
We report on the sequencing and analysis of a 3,557-bp genomic DNA clone that is located between 4.8 and 1.2 kilobase pairs (kb) upstream of the rbcL gene and is capable of complementing a class of cyanobacterium Synechococcus sp. strain PCC7942 mutants requiring a high level of CO2. The upstream 2,704 bp of this sequence is novel, the remaining 852 bp having been reported by other workers. Four new open reading frames (ORFs) have been identified along with putative promoter elements. These ORFs, which could code for proteins of 7, 10.9, 11, and 58 kDa in size, have been named ORF 64, ccmK, ccmL, and ccmM, respectively. The last three have been named ccm genes on the basis that insertional mutagenesis of each produces a phenotype requiring a high level of CO2 (i.e., each produces a lesion in the CO2 concentrating mechanism). The putative gene product for the large ccmM ORF has three internally repeated regions and also has two possible DNA binding motifs. Two defined mutants in the 3,557-bp region, mutants PVU and P-N, have been more fully characterized. The PVU mutant has a drug marker inserted into the ccmL gene, and it possesses abnormal rod-shaped carboxysomes. The P-N mutant is a 2.64-kb deletion of DNA from the same position in ccmL to a region closer to rbcL. This mutant, which has previously been shown to lack carboxysomes and have soluble ribulosebiphosphate carboxylase/oxygenase activity, has now been shown to have a predominantly soluble carboxysomal carbonic anhydrase activity. Both mutants were found to possess carboxysomal carbonic anhydrase activities which are below wild-type levels, and in the P-N mutant this activity appears to be unstable. The results are discussed in terms of the possible interactions of putative ccm gene products in the process of carboxysome assembly and function.